Comparison of manual anthropometry and a mobile digital anthropometric system - Bušic,A.; Bušic, J.; Coleman, J.; Šimenko, J. (Proceedings of the 8th International Conference on Sport Sciences Research and Technology Support, 2020)
With the progress of technology, new digital shape-analysis tools are being developed for use in several different fields. Innovation and market demand has pushed developers to create a portable 3D scanner. The aim of this research was to perform a comparison of a new portable measuring system for digital measurement of anthropometric dimensions of the body, with the system of manual anthropometry. The results show that the Coefficient of determination (R2) was in 7 measurements over 90%, in 6 measurements over 80%, and in 2 measurements above 74.9%. Cronbach Alpha results of compared variables were all over 90%, which show very strong expected correlations. No significant bias between measurement techniques was shown as Bland-Altman plots showed a good agreement between measurement techniques with a small number of outliers. Results provide high validity and accuracy of the new portable scanner when correctly used. However, methods of 3D body scanning and classical anthropometry shou ld not be regarded as interchangeable as there are differences in initial body positions due to the implementation of measurement protocols. Further work is recommended to make the two methods more interchangeable, with the possible usage of corrective coefficients.